Keeping it hot eaudiobook - Landon, Sydney (Breakfast in Bed, 2017)
Zoe Hart owns the coffee shop in one of the hottest upscale resorts in Florida, run by her childhood best friend, Dylan Jackson. Even though Dylan is a workaholic, he still finds time to enjoy the beautiful women who pass through his hotel—all of them except Zoe. She has been in love with Dylan for years without him noticing. But with her thirtieth birthday fast approaching, she realizes she can't keep pining away for a man who doesn't show the merest sign of romantic interest in her. When Zoe launches her plan to shed her tomboy image in Dylan's eyes, she's thrilled once he starts to notice her in a whole new way. But she'll have to face the risk that seducing her best friend might come with lasting changes to their longtime friendship . . .